2018
DOI: 10.1515/libri-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

The Trends of Media Coverage about Libraries in Korea: Using Semantic Network Analysis of Portal News

Abstract: The purpose of this study is to understand the trends and problems of media coverage about Korean libraries by selecting keywords from Korean portal news articles and conducting semantic network analysis. As a result, Korean news reports focus on public libraries rather than school and university libraries. Elsewhere, libraries’ lifelong learning program performance, such as cultural events and educational lectures, are overly biased on press release. In addition, news articles in all kinds of libraries are do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Choi et al (2018) and Kim (2014) analyzed the changes in intellectual structure in the field of Library and Information Science and Sports Sociology, respectively, by dividing the period and observing changes in the ranking of keyword centrality. Cho (2018) also observed changes in intellectual structure through changes in the ranking of centrality of library-related keywords reported in the media using a similar method. The precedence studies described above have identified changes in the intellectual structure just through observing changes in the ranking of the centrality of keywords.…”
Section: Prior Research Reviewmentioning
confidence: 76%
See 2 more Smart Citations
“…Choi et al (2018) and Kim (2014) analyzed the changes in intellectual structure in the field of Library and Information Science and Sports Sociology, respectively, by dividing the period and observing changes in the ranking of keyword centrality. Cho (2018) also observed changes in intellectual structure through changes in the ranking of centrality of library-related keywords reported in the media using a similar method. The precedence studies described above have identified changes in the intellectual structure just through observing changes in the ranking of the centrality of keywords.…”
Section: Prior Research Reviewmentioning
confidence: 76%
“…Usually 0.0-0.1 is almost irrelevant 0.1-0.2 means weak positive correlation, 0.2-0.4 means normal positive correlation, and from 0.4, it means relatively strong positive correlation. There are a number of studies explaining the similarity through correlation coefficients of centrality in different networks (Bae 2015;Cho 2018;Chen et al 2019;Szell et al 2010). In this study correlation analysis was performed by pairing each segment from W1 to W5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It quantifies the degree to which nodes are in the center of nodes through the number of nodes related to each other (Martinus et al, 2015). The higher the proportion of centralized nodes, the higher the centrality of connections (Cho, 2018). Researchers and leaders can immediately determine the connectivity and importance between words through the size of the nodes and connecting lines visualized through network analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Textom has frequently been used by academic journals in Korea (M. S. S. Park & Hwang, 2017) as well as international journals (Cha et al, 2017;Cho, 2018). Through Textom, this study collected text data on the RSF in online news and blogs, extracted the nouns, and acquired 4,498 items, including 88,168 words (Table 2).…”
Section: Data From Textommentioning
confidence: 99%